(untitled) (Bangladesh Journal of Agricultural Research, 2008)
Field experiments were conducted at Joydebpur, Jessore, and Ishurdi of Bangladesh Agricultural Research Institute (BARI) during rabi seasons of 2002- 03 and 2003-04 to analyze the production factors limiting performance of yield and yield attributes of lentil. The treatments were, T1 = complete package of production factors (CPP), T2 = CPP with 30-day delay sowing, T3 = CPP excluding chemical fertilizer, T4 = CPP in addition to cowdung only as fertilizers, T5 = CPP excluding N, T6 = CPP also with broadcast seeding, T7 = CPP excluding plant protection measures, and T8 = CPP excluding seed treatment. Averaged over locations, CPP resulted in significantly higher seed yield (1915 kg/ha) and gross margin (Tk. 31043/ha) compared to any other treatment exercised in the study. Response of organic manure contribution was positive to increasing seed yield (16%). Use of inoculum (instead of N) under CPP gave statistically identical yield in all three locations. Seed yield decreased significantly (11-42% at Joydebpur, 10-37% at Jessore, and 9-41% at Ishurdi) when any of the production factors was withdrawn from CPP irrespective of locations. The maximum reduction in mean seed yield was recorded due to delayed sowing (40%) followed by withdrawing of chemical fertilizers (22%), using organic manure only (20%) and broadcast seeding (15%), without plant protection measures (15%), and using non-treated seeds (14%), respectively. Gross return also reduced significantly (15-44%) when any of the management practices was withdrawn from CPP. The results revealed that delay in sowing, no use of plant protection measures, chemical fertilizers and seed treatments were the production factors limiting yield of lentil. Bangladesh J. Agril. Res. 32(4) : 593-601